Types Of Rasulullah’s Educational Media in The Perspective of Bukhari Hadith - Junaidi Arsyad; Maisaroh Ritonga; Syamsu Nahar (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research means to defeat the issue of the absence of instructive media and the negligible use by instructors in educating and learning exercises, particularly PAI learning in schools or madrasas. This exploration makes sense of that well before this time different Rasulullah saw. have involved different sorts of instructive media in learning exercises which are arrangements in conquering the above issues, which are tracked down in a few hadiths in the book Jami' As-Sahih by Imam Bukhari. This exploration is a sort of library research. The information legitimacy strategy is done with the level of trust (validity) and constancy by examining research information. Information examination utilized in this exploration is content examination. The consequences of this review are that overall the kinds of instructive media involved by the witnesses in conveying material in the educational experience are characterized into 4 sorts of media, to be specific: a. Human-based media incorporates: pretending, Rasulullah saw. utilizing the tongue, fingers, hands, nose, knees and the tips of the toes. b. Print media, Rasulullah saw. using mail. c. Visual media, including: pictures, sun, moon, trees and plants and downpour, and d. sound media. Rasulullah saw. using sound media by raising his voice and utilizing the word قرا in a few hadiths.